2015
DOI: 10.1007/s00586-015-4033-8
|View full text |Cite
|
Sign up to set email alerts
|

Depression is associated with increased incidence of osteoporotic thoracolumbar fracture in postmenopausal women: a prospective study

Abstract: Depression is associated with a higher risk of thoracolumbar fracture, with more fracture pain and with lower quality of life in the 2 months following fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…Feelings of guilt are associated with other depressive symptomatology, 50 while recent studies have associated depression with bone fracture risk and mental health. [51][52][53] Our BIA-ACC ® platform results of the MUS questionnaire confirmed the aforementioned studies and provided an easy, reliable screening test in postmenopausal women (supplementary information).…”
Section: Discussionsupporting
confidence: 77%
“…Feelings of guilt are associated with other depressive symptomatology, 50 while recent studies have associated depression with bone fracture risk and mental health. [51][52][53] Our BIA-ACC ® platform results of the MUS questionnaire confirmed the aforementioned studies and provided an easy, reliable screening test in postmenopausal women (supplementary information).…”
Section: Discussionsupporting
confidence: 77%
“…Previous studies have demonstrated a positive relationship between depressive disorders and a higher risk of vertebral fracture 18,20,21, but other research has reported different findings 19,22. However, our results support the notion that the risk of vertebral fracture is significantly higher in patients with a depressive disorder.…”
Section: Discussionsupporting
confidence: 64%
“…The long-term complications of vertebral fractures include kyphosis, deconditioning, insomnia, and depression 17. However, studies on the relationship between depressive disorders and the incidence of vertebral fracture have yielded conflicting results 18,19.…”
Section: Introductionmentioning
confidence: 99%
“…There is a relationship between depression and locomotive disorder, osteoporosis, lumbar spinal stenosis, and fracture [2931]. Endocrine factors such as depression-induced hypersecretion of corticotropin-releasing hormone and hypercortisolism, hypogonadism, growth hormone deficiency, and increased concentration of circulating interleukin 6 might play a crucial role in the bone loss observed in subjects suffering from major depression [29].…”
Section: Discussionmentioning
confidence: 99%